Afetividade e processo de ensino e aprendizagem: narrativas sobre a prática docente - BARBOSA, Hevelly Sousa (2023)
The study has as its central theme the discussion about the role of affectivity in the teaching and learning process based on teaching practice. I assume the theoretical and methodological principles of narrative research, understanding that narrative is the best way to understand and study the real-life environment through experience reports. Investigating how teachers use affectivity in their teaching practice constitutes the general objective and, specifically, identifying aspects of affectivity assumed and present in the interaction between teacher and student in the pedagogical relationship, in addition to systematizing the repercussions of aspects of affectivity in students' learning. Three teachers who work in Early Childhood Education in a private institution in the city of Castanhal-PA participated in the research. The interviews were carried out with the purpose of identifying the relevance of affectivity in the teaching-learning process for the teachers and how affective relationships were used in teaching practice. Thus, through this research, the importance of affection within the classroom environment and, more precisely, in the relationship between teacher and student was verified, since affectivity and cognition are not dissociated. Therefore, the affects permeated in this interpersonal relationship can generate decisive impacts on the teaching and learning process.